Mango Seeds as Raw Materials for Dextrin - Munawar Ali (Global Writing Academica Researching & Publishing, 2023)
Wasted seeds are sometimes scattered all over the place during the mango season to spoil the beauty and pollute the environment. Mango seeds can be processed into dextrin, so efforts must be made to process them in order for them to be useful. Specifically, by hydrolyzing mango seed flour with an HCl catalyst. The mango seed flour is 20 grams in weight; 10 milliliters of HCl are added, and water is added until the volume reaches 200 milliliters. Additionally, heat at the temperature of heating: 70 o C; 80oC; _90°C; 100°C; 110°C, and the concentration of HCl: 0.1N; 0.15N; 0.20N; 0.25N; Hydrolysis time was used to produce 0.3N: 15 seconds; 20 seconds; 25, 30, and 35 minutes, respectively. As a result, it is anticipated that a lot of dextrin yields will be obtained. The treatment that was used in the previous study yielded the best results, with a dextrin yield of 8.16 percent at a hydrolysis temperature of 100 degrees Celsius, a concentration of 0.25 N HCl, and a hydrolysis time of 35 minutes.